Wuhan University Journal of Natural Sciences - Hu, Min.; Shu, Hongbing; SpringerLink (Online service) (Wuhan : Wuhan University : Imprint: Wuhan University, co-published with Springer.)
Wuhan University Journal of Natural Sciences aims to promote rapid communication and exchange between the world and Wuhan University, as well as other Chinese universities and academic institutions. It mainly reflects the latest advances being made in many disciplines of scientific research in Chinese universities and academic institutions. The journal also publishes papers presented at conferences in China and abroad. The multi-disciplinary nature of Wuhan University Journal of Natural Sciences is apparent in the wide range of articles from leading Chinese scholars. This journal also aims to introduce Chinese academic achievements to the world community, by demonstrating the significance of Chinese scientific investigations. The featured topics include the various aspects of life science, material science, and computer science.
Keywords: Computer science; Life sciences; Materials science; Life Sciences, general; Materials Science, general; Computer Science, general